The Use of Enterprise Architecture to Increase the Production Processing Case Study in Textile Production Company - Ailsa Amelia, Lorio Purnomo, Gunawan Wang, Nilo Legowo (International Journal of Advanced Science and Technology, 2020)
Enterprise Architecture is used to support the Company in the production process in the textile industry. The Textile Company takes the ISO 9001 approach, in the production process, and in applying the Management Information System to the weaving division to replace the conventional process. In its implementation, not all parties can accept changes in technology. So this research proposes the concept of Enterprise Architecture Zachman, so as to produce business management changes to the Production Process, then using the ISO 9001 approach is expected to implement a production system process that is more organized and in accordance with ISO 9001 quality standards. Both of these approaches as a guide for management to encourage Textile companies to implement and make changes to the business model that is arranged in the management system of the Textile Company. Keywords: Enterprise Architecture, Zachman, ISO 9001, Management System, Weaving